2012
DOI: 10.1002/adhm.201200006
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Solid Lipid Nanoparticle Formulation for Active Targeting to Tumor αvβ3 Integrin Receptors Reveals Cyclic RGD as A Double‐Edged Sword

Abstract: The overexpression of α(v) β(3) integrin receptors on tumor cells and tumor vascular endothelium makes it a useful target for imaging, chemotherapy and anti-angiogenic therapy. However integrin-targeted delivery of therapeutics by nanoparticles have provided only marginal, if any, enhancement of therapeutic effect. This work was thus focused on the development of novel α(v) β(3) -targeted near infrared light-emitting solid lipid nanoparticles (SLN) through conjugation to the α(v) β(3) integrin-specific ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 43 publications
3
62
1
Order By: Relevance
“…[56] In contrast, the RGD-TM and RGD-TL particles would be expected to bind two or more integrins simultaneously. Furthermore, recent studies have suggested that RGD ligands are useful for the imaging of tumor neovasculature but that the targeting ligand may not increase tumor homing [53] but instead may increase overall tissue distribution, [57] which is also consistent with our findings (Figure 2C). Effective integrin targeting is highly dependent on the ligand density.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…[56] In contrast, the RGD-TM and RGD-TL particles would be expected to bind two or more integrins simultaneously. Furthermore, recent studies have suggested that RGD ligands are useful for the imaging of tumor neovasculature but that the targeting ligand may not increase tumor homing [53] but instead may increase overall tissue distribution, [57] which is also consistent with our findings (Figure 2C). Effective integrin targeting is highly dependent on the ligand density.…”
Section: Resultssupporting
confidence: 92%
“…Nanoparticles decorated with RGD ligands have previously been shown to accumulate in the organs of the macrophagocytic system, reflecting structural differences in the protein corona compared to stealth nanoparticles. [57] Rapid tissue clearance is consistent with our previous TMV biodistribution studies, [62] and makes TMV particularly attractive for molecular imaging and drug delivery approaches where rapid tissue clearance is necessary.…”
Section: Resultssupporting
confidence: 81%
“…Folate and cRGD are frequently used as ligands to target cancer cells overexpressing folate receptors 33 and neovasculature of tumors, 34 respectively. Amine-terminated betaine polymer (pCB) was synthesized as a new stealth coating with a potent anti-fouling effect.…”
Section: Resultsmentioning
confidence: 99%
“…Surface conjugation of antibodies or proteins on the nanoparticles may enhance tumor recognition and binding, but it may increase chances of being removed from the circulation by the RES. For example, nanoparticles (liposome, SLN or nanoparticle coated with chitosan) conjugated with integrin ( α v β 3 ) specific ligand cyclic Arg-Gly-Asp Peptide ( c RGD) showed much greater hepatic uptake than non-targeted nanoparticles, resulting in lower tumor accumulation [154-156]. In addition to higher liver uptake of nanoparticles observed with targeting moieties than non-targeted nanoparticles, the difference in targeting receptor expressions between rodents for preclinical studies and humans.…”
Section: Technical Challenges and Limitationsmentioning
confidence: 99%